Ethics of modern business - Adams, Morrison Carpenter (My University, 1899)
Introduction: Necessity of ethical principles to a true industry. A the present time the business of the world has developed to such an extent, its field has become so broad and its influence so powerful, that the principles by which it is managed, the laws by which it is governed, and the effects produced by it should be a subject for careful thot and action by every intelligent person. Necessity of ethical principles to a true industry. That the world’s population is not deriving much benefit from its gigantic system of industry, cannot be questioned for a moment. The advancement which it has wrought on civilization is not to be underestimated. But along with the good points of modern business, the thoughtful and observant person cannot help but see, that at best from an ethical standpoint,- there are to be seen many faults which promise to be and are now, opposed to the continuous progress and growth of individuals, of states, of nations, and of the whole world.
Citation: Adams, Morrison Carpenter. Ethics of modern business. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Necessity of Ethical Principles; Illustrations of Departure from Ethics; Theses; Manuscripts (documents)